(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Issues related to women’s rights have been heavily debated in recent times. All cultures, but theWest in particular, have rethought women’s conventional roles. Because of this, women’s involvement inthe workforce, government, and society as a whole has increased dramatically. The reevaluation includesa discussion of the place of women in the world’s main religions. Among Christian countries, the questionof whether or not women should be ordained as clergy has become more controversial and perhapspotentially schismatic. That being the case, this is an appropriate moment to reflect on Buddhism’streatment of women. There are a number of possible readings of the Buddhist perspective on women’srole in society. By comparing the position of women in religious and secular life in India before and afterthe advent of Buddhism, we may gauge the extent to which the Buddha’s teachings prompted a radicalshift in social norms.